Tradisi Perjodohan pada Masyarakat Bugis di Kecamatan Ladongi: Deskripsi, Dampak, dan Perspektif Hukum Islam - Rasak, Abdul (IAIN Manado, 2023)
This research examines the tradition of arranged marriages in the Bugis community in the Ladongi Subdistrict, East Kolaka Regency, focusing on description, impact, and analysis from the perspective of Islamic law. The study employs an empirical legal or socio-legal research approach with a descriptive-qualitative method. Through direct observation and interviews on the practice of arranged marriages and the application of Islamic law, the research findings indicate that the tradition of arranged marriages still exists due to specific factors and motives. The matchmaking process involves procedural stages that consider parents' choices as the best for their children. Positive outcomes occur when the selected partners meet the criteria set by parents and are accepted willingly by the children. However, negative impacts arise when children are unwilling to accept the chosen partner, feel afraid to express their disagreement, or when parents force the marriage. From the perspective of Islamic law, arranged marriages are considered permissible (mubah), and parents do not have the right to force their children into marriage. The research suggests that the tradition of arranged marriages can be carried out with the willingness and sincerity of the children, avoiding coercion that contradicts Islamic principles.Keywords: Arranged Marriages Tradition; Bugis Tribe; Islamic Law.ABSTRAK Penelitian ini mengkaji tradisi perjodohan pada masyarakat Bugis di Kecamatan Ladongi, Kabupaten Kolaka Timur, dengan fokus pada deskripsi, dampak, dan analisis dari perspektif hukum Islam. Penelitian ini menggunakan pendekatan penelitian hukum empiris atau socio-legal research dengan metode deskriptif-kualitatif. Melalui observasi langsung dan wawancara terhadap praktik tradisi perjodohan dan penerapan hukum Islam, hasil penelitian menunjukkan bahwa tradisi perjodohan masih eksis karena faktor dan motif tertentu. Proses perjodohan melibatkan tahapan prosedur yang mempertimbangkan pilihan orang tua sebagai yang terbaik bagi anak. Hasil positif terjadi saat pasangan yang dipilih memenuhi kriteria baik orang tua dan diterima tanpa paksaan oleh anak. Namun, dampak negatif muncul ketika anak enggan menerima pasangan yang dipilihkan, merasa takut untuk mengekspresikan ketidaksetujuannya, atau saat orang tua memaksa pernikahan. Dari perspektif hukum Islam, perjodohan dianggap mubah dan orang tua tidak berhak memaksa anak untuk menikah. Hasil penelitian menyarankan bahwa tradisi perjodohan dapat dilakukan dengan kerelaan dan keikhlasan dari anak, menghindari paksaan yang bertentangan dengan prinsip-prinsip Islam.